Hermenêutica e decisão judicial: os rumos do processo penal diante dos discursos maniqueístas potencializados na sociedade em rede - Castro, Roger de Moraes de (2018)
The present work aims at treating to what extent the Manichean discourses promoted by the network society influence the decision making process in the environment of criminal procedural law considering autonomy itself. This task began with an analysis of the facets of the criminal process, seeking to ratify the adoption of the accusatory procedural model by the Constitution. From there, the understanding of criminal procedural law from the Philosophical Hermeneutics proposed by Gadamer and worked by Streck. Continuing, the thematic of the society in network, from Castells is approached. This is justified by the fact that current society has undergone significant changes, mainly due to the contribution of the Internet and the new means of Information and Communication Technology, which have substantially changed the standards of sociability, communication and information. In this scenario, some of the changes and social manifestations occurring with the proliferation of the internet and the media are recorded, with the main focus of the theoretical ties of the present research being the "judgments", the debates on criminal and procedural criminal matters and the form with which the Judiciary has been seen by society. After the first chapter, we will understand the autonomy of the law and the judicial judicial decision constitutionally correct from the armouring made by legal hermeneutics and the integrative theory of Dworkin, in the sense of the application of law as integrity and coherence. In the face of this, one will seek to ascertain the democratic meaning of a judicial decision handed down in a process with democratic pretensions. Understanding the responsibility of judges at the time of criminal procedural decisions, reflecting on the impossibility and unconstitutionality of judicial decisions based on elements external to the law, especially in the field of morality, which end up preying on the law. Finally, it is demonstrated the influence of the Manichean discourses in the judicial decisions, through some judged ones.